Relationship Between CO₂ Emissions and Trade: The Case of the EU - Dušan Steinhauser; Zuzana Kittová; Lucia Khúlová (Intereconomics, 2024)
Understanding the relationship between international trade and CO2 emissions is crucial for designing appropriate measures to address climate change. This article focuses on CO2 emissions as one of the trade flow determinants of the EU countries, along with other factors including remoteness, labour productivity, real effective exchange rates, and research and development expenditures. The authors conclude that EU exports and imports are growing to or from those partner countries whose CO2 emissions are rising. Furthermore, the growing similarity between the emissions of the EU and partner countries supports mainly the growth of EU exports and points to the slowdown in the growth of partners' emissions intensity. The existence of a relationship between CO2 emissions and EU trade is important for the expected effects of the Carbon Border Adjustment Mechanism to materialise. Thus, this study confirms the assumption that emissions can be reduced in EU partner countries through trade and trade measures.
Keywords: F13; F18; 330; Foreign trade; Greenhouse gas emissions; Climate change; EU countries; Außenhandel; Treibhausgas-Emissionen; Klimawandel; EU-Staaten